(untitled) (Elmergib Journal of Human Sciences, 2026)
This research discusses the Arab-Islamic cultural manifestations that emerged in East Africa. The settlement of Arab Muslims on the East African coast led to the spread of Arab-Islamic culture and the emergence of a new society based on Islamic traditions and local African customs that Islam refined and imbued with its standards and principles. This research clarifies the centers of Islamic propagation that represented the most important of these manifestations, namely the mosques, zawiyas, and ribats that preachers used for preaching and guidance. Over time, these became intellectual and scientific places where scholars, jurists, and teachers would come and hold their circles in various aspects of knowledge. This research also includes useful references to the efforts towards eliminating the slave trade in East Africa and consolidating adherence to Islamic customs, traditions, and norms there. This research also addresses the emergence of new systems of governance and administration represented in some Islamic states, kingdoms, and emirates .